The golden spoon eaudiobook A novel. - Maxwell, Jessa (Simon & Schuster Audio, 2023)
NATIONAL BESTSELLER "This delicious combination of Clue and The Great British Bake Off kept me turning the pages all night!" —Janet Evanovich, #1 New York Times bestselling author Only Murders in the Building meets The Maid in this "deliciously entertaining whodunit" (Sarah Penner, New York Times bestselling author) where someone turns up dead on the set of TV's hottest baking competition—perfect for fans of Nita Prose, Richard Osman, and Anthony Horowitz. Every summer for the past ten years, six awe-struck bakers have descended on the grounds of Grafton, the leafy and imposing Vermont estate that is not only the filming site for "Bake Week" but also the childhood home of the show's famous host, celebrated baker Betsy Martin. The author of numerous bestselling cookbooks and hailed as "America's Grandmother," Betsy Martin isn't as warm off-screen as on, though no one needs to know that but her. She has always demanded perfection, and gotten it with a smile, but this year something is off. As the baking competition commences, things begin to go awry. At first, it's merely sabotage—sugar replaced with salt, a burner turned to high—but when a body is discovered, everyone is a suspect. A sharp and suspenseful thriller for mystery buffs and avid bakers alike, The Golden Spoon is "as addictive as bingeing your favorite culinary competition and as satisfying as a piece of your favorite cake" (Kellye Garrett, author of Like a Sister ).